KURIKULUM PAI TEMATIK DALAM PEMBENTUKAN AKHLAQ ANAK SHOLEH PADA USIA DINI: (Studi Multi Kasus di TK-IT Buah Hati dan RA Bina Insani Sintang) - Akhmad Hasan; Aslan Aslan; Ubabuddin Ubabuddin (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
This research is motivated by the curriculum as one of the main points of reference in implementing education. The author's meticulous curriculum is the Thematic Islamic Religious Education curriculum developed by the institution. In this case teachers, foundation administrators, school committees, community leaders and guardians of students. Institutions that become the object of research is TK-IT Buah Hati and RA Bina Insani Sintang. TK-IT Buah Hati and RA Bina Insani Sintang are one among the educational institutions based Islamic values are automatically used, the curriculum used is self-developed in accordance with the vision and mission of the institution. Data was collected by observation, interviews, and documentation. This research generally shows that the process of planning the Thematic PAI curriculum, implementing the Thematic PAI Curriculum and evaluating the Thematic PAI curriculum at TK-IT Buah Hati and RA Bina Insani Sintang have been carried out very well so as to produce pious, intelligent and independent children.